Literature Review: Asuhan Keperawatan Pada Pasien Dengan Risiko Perilaku Kekerasan Menggunakan Teknik Komunikasi Terapeutik - Yuke Septiana Ida Lidiawati; Christina Trisnawati; Fida Dyah Puspasari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background : The prevalence of depression in residents Indonesia is â‰¥ 15 years old (9%) and the prevalence of mental and emotional disorders in the form of stress, anxiety and depression covers 9.8%, Violent behavior is a response to stressors experienced by someone, which can be reflected in actual acts of violence against oneself or others, verbally or non-verbally, which aim to hurt people physically and psychologically. Therapeutic communication is conscious communication, directed and the core of its activities is for the patient's recovery and is a professional communication that leads to the goal of healing the patient (Mundakir, 2006). Objective: Knowing the illustrated description of Nursing Care for Patients with the Risk of Violent Behavior using Communication Techniques. Method: method used by researchers is descriptive research in the form of a literature review. Results: results of a literature review of 2 journals related to psychiatric nursing care with a risk of violent behavior. Conclusion: Based on the results of the observations that the researchers made of the studies carried out by the two researchers, the similarities were found, namely carrying out a thorough assessment both based on the patient's main complaint being taken to the hospital due to a tantrum when angry, predisposing factors, namely the patient has a history of repeated treatments and the precipitation factor is the patient not routinely taking medication.